(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
In this article, the education and upbringing of children in need of special assistance is about helping to adapt the problems of teaching them to read and write to social life, effective implementation of these tasks, practical assistance to special field workers and parents of disabled children. such responsible work is thought about.